2021
DOI: 10.1101/2021.06.16.448227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripheral CB1 receptor blockade acts as a memory enhancer through an adrenergic-dependent mechanism

Abstract: Peripheral inputs to the brain continuously shape its function and adjust non-emotional memory, but the mechanisms involved are not fully understood. Cannabinoid type-1 receptors (CB1Rs), widely distributed in the organism, are well recognized players in memory performance and their systemic modulation significantly influence memory function. By assessing non-emotional memory in mice, we found a relevant role of peripheral CB1R in memory persistence. Indeed, peripherally restricted CB1R antagonist AM6545 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 63 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…Regarding emotional memory, we reported that a single administration of AM6545 after the first extinction session in the context fear conditioning, promoted freezing behavior when memory was assessed the next day. However, freezing behavior was reduced when assessed during the subsequent extinction sessions (Martínez-Torres et al, 2023). In the present study, we showed that administering AM6545 after every extinction session maintains high freezing levels across days, pointing to a persistent effect of the repeated exposure to AM6545 in emotional memory.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Regarding emotional memory, we reported that a single administration of AM6545 after the first extinction session in the context fear conditioning, promoted freezing behavior when memory was assessed the next day. However, freezing behavior was reduced when assessed during the subsequent extinction sessions (Martínez-Torres et al, 2023). In the present study, we showed that administering AM6545 after every extinction session maintains high freezing levels across days, pointing to a persistent effect of the repeated exposure to AM6545 in emotional memory.…”
Section: Discussionsupporting
confidence: 57%
“…Our previous research showed that AM6545-memory improvement after a single administration was dependent on an adrenergic mechanism given that AM6545 mnemonic effect was prevented by the peripherally restricted β-adrenergic antagonist sotalol (Martínez-Torres et al, 2023). The fact that here sotalol pretreatment significantly reduced the mnemonic effect of sub-chronic AM6545 points to a relevant role of the peripheral adrenergic tone.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations